Perception of the professors from the School of Economics at the National University of Colombia about the use of the mathematics in their discipline (2017)
This paper is the result of a research that aims to know the perspective of some professors from the School of Economics at the National University of Colombia through the application of a questionnaire, in order to make a critical diagnosis, by analyzing the responses obtained, taking into account the concepts of acceptability, use, relevance and scientific nature that each one of the professors have about mathematics in economics . Besides, it also aims to make a theoretical review such as Gabriel Misas Arango, José Félix Cataño, among others.